Brazil Background Study for a National Rural Electrification Strategy : Aiming for Universal Access - World Bank (Washington, DC, 2014)
According to data from the 2000 Census, about 27 percent of Brazil's rural population still lacks access to electricity. This represents more than 2.5 million households. In comparison, the same statistic is about 20 percent in Argentina, Chile, and Mexico. The figure includes the achievements of the Luz no Campo program, which will complete its first implementation phase with more than 600,000 new connections, but also users with precarious or illegal access to electricity. One important message from the census data is that the absence of a basic and modern energy source affects particularly low-income families, which end up paying a much higher price for energy service per kWh (because they use batteries) and living with poor quality lighting (from kerosene or LPG lamps), or both.